(3RhGgQ GdacQ hLhGgQ GdabQs - (3eMeO Hf Ydj Hf YHO GdQMef GdeQGOj, CHh GdYdGA , GHf GdeQGHWs
(3ChdgG (B:s
(3CMeO Gdg JYGdi MeOkG ehUhdkG Ke CcJH Ef TGA Gddg JYGdi ai gPG GdSaQ GdKGdK ef cJGH RhGgQ GdacQ hLhGgQ GdabQ eGjJYdb HEPjGdg GdeJbOejf s
(3BNQgG (B:s
(3hgPG BNQ GdCQHYI YTQ aUdkG GdJi bSeJ ai gPG GdeLehY hJe ai GdQhHjJ hGdMeO ddg s
(3eLehYI eNJGQGJ VYQjg cGf GdeDda MjkG SfI (B721(3g` s
(3HChdgG CSeGA TYQGA GdeLehYI s
(3hHBNQgG eYGQVI hSeGYgG HJGQN (B721(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs